Experimental parameters optimization of instrumental neutron activation analysis in order to determine selected elements in some industrial soils in Turkey - Haciyakupoglu, Sevilay; Esen, Ayse Nur; Erenturk, Sema (Pergamon-Elsevier Science Ltd, 2014)
The purpose of this study is optimization of the experimental parameters for analysis of soil matrix by instrumental neutron activation analysis and quantitative determination of barium, cerium, lanthanum, rubidium, scandium and thorium in soil samples collected from industrialized urban areas near Istanbul. Samples were irradiated in TRIGA MARK II Research Reactor of Istanbul Technical University. Two types of reference materials were used to check the accuracy of the applied method. The achieved results were found to be in compliance with certified values of the reference materials. The calculated En numbers for mentioned elements were found to be less than 1. The presented data of element concentrations in soil samples will help to trace the pollution as an impact of urbanization and industrialization, as well as providing database for future studies. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Industrial Soil; Inaa; Gamma Spectroscopy; Uncertainty; Heavy-Metal Contamination; Urban Soil; Trace; Selenium; Barium; Brazil; China; Inaa; Diet; City